MEMES, MEMES EVERYWHERE: aprendizagem colaborativa de língua inglesa através da leitura e produção de memes - Nunes, Mariana Backes (Universidade do Vale do Rio dos Sinos, 2020)
The social and communication changes of recent times gave space for the advent of new technologies that modified the social practices of reading and writing, allowing the emergence of new textual genres, such as memes, the theme of this research. Memes can be defined as internet practices that spread in a viral manner, repeating a basic formal model. They are usually texts written by amateurs, characterized by intertextuality, juxtaposition, and, mainly, humor. Therefore, because it is a multimodal textual genre from the internet, we consider the concepts of new literacies, suggested by Lankshear and Knobel (2007), and multimodality, explored by Kress (2003), as well as sociocultural theory of learning, based on the studies of Vygotsky and his followers (LANTOLF, 2011; SWAIN, 2000), since collaboration plays a fundamental role in the literate practices of the 21st century. We thus sought to understand the role of these elements in the English language classroom by investigating how the processes of reading and collaborative production of memes by students, future teachers of the same language, occur. To do that, the methodology used in this work is qualitative-interpretative, having Letras students with an intermediate level of proficiency in English as participants of the research. For that generation, collaborative tasks were developed in which the students read and produced memes having university life as the central theme. At the same time, in the data analysis, moments of collaboration between the students and between the students and the teacher are pointed out, as well as a mapping of students' previous knowledge about memes. The research aimed to encourage the use of digital technologies as mediators of foreign language teaching and learning so that preservice teachers are challenged and instigated to seek more information about the new literacies in order that we can see them more present in the classrooms in the future.
Keywords: Língua estrangeira; Ensino e Aprendizagem; Novos letramentos; Colaboração; Memes; Foreign language; Teaching and learning; New literacies; Collaboration; Memes; ACCNPQ::Lingüística, Letras e Artes::Lingüística